Case Report: Spesolimab for pyoderma gangrenosum in an undifferentiated oligoarthritis patient receiving anti-IL-17 therapy - Xin, Weiwei; Gu, Liyang; Du, Fang; Li, Ting; Ye, Shuang (Frontiers in Immunology, 2025)
Pyoderma gangrenosum (PG) is a classic neutrophilic dermatosis often associated with inflammatory conditions, frequently leading to misdiagnosis and delayed treatment. Drug-induced and postoperative are two potential triggers of PG. A 70-year-old woman, who had been treated with Ixekizumab for undifferentiated oligoarthritis, presented with cribriform violaceous ulcers on her right posterior ankle after 8 months of debridement. A skin biopsy revealed a predominant neutrophilic infiltrate with no signs of infection after extensive microbiology investigation. The patient was diagnosed with pyoderma gangrenosum (PG) and achieved remission after receiving three doses of 900 mg intravenous Spesolimab every 4 weeks, along with discontinuation of Ixekizumab. The case highlights the successful use of Spesolimab (anti-IL36R) in treating PG and explores the potential “paradoxical phenomenon” linked to anti-IL-17 therapy, providing novel insights into immune dysregulation and therapeutic strategies.